2010
DOI: 10.1074/jbc.m109.051128
|View full text |Cite
|
Sign up to set email alerts
|

Conserved Negative Charges in the Transmembrane Segments of Subunit K of the NADH:Ubiquinone Oxidoreductase Determine Its Dependence on YidC for Membrane Insertion

Abstract: All members of the Oxa1/Alb3/YidC family have been implicated in the biogenesis of respiratory and energy transducing proteins. In Escherichia coli, YidC functions together with and independently of the Sec system. Although the range of proteins shown to be dependent on YidC continues to increase, the exact role of YidC in insertion remains enigmatic. Here we show that YidC is essential for the insertion of subunit K of the NADH: ubiquinone oxidoreductase and that the dependence is due to the presence of two c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
24
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 51 publications
0
24
0
Order By: Relevance
“…For instance, TM regions of membrane proteins may contain functionally important polar residues, which might be unstable in the lipidic environment upon release from translocons until assembling with a partner TM polypeptide also containing complementary polar residues (30,31). It is tempting to speculate that the hydrophilic cavity of YidC provides a transient docking surface that binds a newly inserted TM segment before it finds a partner of assembly.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, TM regions of membrane proteins may contain functionally important polar residues, which might be unstable in the lipidic environment upon release from translocons until assembling with a partner TM polypeptide also containing complementary polar residues (30,31). It is tempting to speculate that the hydrophilic cavity of YidC provides a transient docking surface that binds a newly inserted TM segment before it finds a partner of assembly.…”
Section: Discussionmentioning
confidence: 99%
“…NuoK is a small membrane subunit K of the NADH dehydrogenase (Fig. 7A), requiring both SecYEG and YidC for efficient membrane insertion (13). To study the in vitro membrane insertion of NuoK, YidC together with SecYEG were integrated into liposomes to obtain SecYEG-YidC-containing proteoliposomes (Fig.…”
Section: The Cytoplasmic Loop C2 and The C Terminus Of Yidc Are Requimentioning
confidence: 99%
“…E. coli YidC is essential for cell viability (5) and has been shown to function as an insertase in the membrane insertion of the filamentous phage Pf3 coat and M13 pro-coat proteins (5,6) and the endogenous substrates F 0 c (7), MscL (8,9), and TssL (10). In cooperation with the Sec translocase, YidC assists in the membrane insertion of CyoA (11,12), NuoK (13), and F 0 a and F 0 b subunits of F 1 F 0 ATPase (14), and the translocation of the periplasmic loop 1 and loop 2 of TatC (15). It also acts as a chaperone in the folding of lactose permease LacY and MalF (16,17).…”
mentioning
confidence: 99%
“…Here, YidC is required for the insertion of the N-terminal region of CyoA into the membrane, followed by the translocation of the more complex C-terminal domain by the Sec translocon (4,9,43). While YidC can act in concert with the Sec translocon, other studies have shown that YidC also can function as an independent insertase for small proteins, such as the M13 and Pf3 phage coat proteins, the subunits a and c of the F 1 F o ATPase (F o a and F o c), and subunit K of the NADH dehydrogenase complex (27,30,31,46). It has been shown that both aerobic and anaerobic respiratory chain complexes are affected in YidC-depleted cells (27,28,46), resulting in a reduction of the proton-motive force (PMF).…”
mentioning
confidence: 99%
“…While YidC can act in concert with the Sec translocon, other studies have shown that YidC also can function as an independent insertase for small proteins, such as the M13 and Pf3 phage coat proteins, the subunits a and c of the F 1 F o ATPase (F o a and F o c), and subunit K of the NADH dehydrogenase complex (27,30,31,46). It has been shown that both aerobic and anaerobic respiratory chain complexes are affected in YidC-depleted cells (27,28,46), resulting in a reduction of the proton-motive force (PMF). PMF reduction leads to a strong upregulation of the stress response protein PspA, which is part of the Psp shock response thought to help maintain the PMF upon membrane stress (5,17,50).…”
mentioning
confidence: 99%